Assisted reproductive technologies for women with rheumatic AID. (April 2020) - Lockshin, Michael D.
Abstract: Assisted reproductive technology (ART) procedures are safe for women with rheumatic autoimmune diseases (rAID) when illness is inactive. Medications incompatible with pregnancy should be replaced with alternative pregnancy-compatible medications months before planned ART procedures to allow time to verify the substitute medication's efficacy and tolerability. Medications compatible with pregnancy should be continued, as should anticoagulation (warfarin changed to low-molecular-weight heparin) before pregnancy begins. Protocols that provide details for specific medications are available. All patients with rAID should be screened for diagnosis-relevant organ system damage, and those intending to carry their own pregnancies must be tested for aPL and anti-Ro/La autoantibodies. Patients with organ damage and/or positive tests for aPL and anti-Ro/La should be counseled about fetal and maternal risks, including implications to the child and family of maternal disability or death. Sperm donors with rAID may need to discontinue medications. REI and physicians treating patients with rAID (usually rheumatologists) must work together to plan and accomplish ART. Highlights: ART procedures are safe in rAID patient with inactive illness. Some medications may need to be discontinued. All rAID patient should be screened for renal, cardiac, and pulmonary insufficiency. SLE, RA, and Sjogren's patients should be screened for antphospholipid and anti-Ro/La antibodies.